Проблеми застосування IT інструментів для використання методу формування ціннісної пропозиції - Потапенко, А. О. (ХНУРЕ, 2024)
The purpose of the work is to compile tasks for creating a value proposition using IT tools. A value proposition describes exactly how a product or service will help customers solve problems and meet needs. The list of tasks should include analysis of customer preferences and assortment analysis. The result of the method is to identify the basic needs of customers, describe the problems they face, identify their expectations and form a map of the manufacturer's value. Thus, the use of IT tools to form a value proposition allows companies to track real customer needs and remain competitive in the market.
Keywords: ціннісна пропозиція; IT інструмент